Linear morphea - A case treated with calcipotriol and betamethasone dipropionate. - Santos, G.; Sousa, L.; João, A.; Paiva Lopes, MJ. (European Journal of Pediatric Dermatology, 2012)
An 11-years-old Caucasian girl referred because of an induration of the left upper limb. On physical examination there was a linear, hypopigmented, poorly defined, hairless, indurated on palpation plaque with peripheral erythema, extending from the shoulder to the wrist (Fig. 1). A skin biopsy showed thickened collagen fibers in the dermis, extending deep into the hypodermis and perivascular and periadnexal lymphocytic infiltrate (Fig. 3). The clinical and histological findings led to diagnose linear morphea. There were no autoantibodies and multiple test for Lyme borreliosis were negative. The patient was treated with calcipotriol hydrate 50 μg/g - betamethasone dipropionate 0.5 mg/g ointment once daily, 3 weeks in a month, for one year and later 2 weeks in a month for 4 months. After 16 months of treatment, a marked improvement was noticed.